Diversity training that generates real change : inclusive approaches that benefit individuals, business, and society - Rodgers, James O.; Kangas, Laura L. (Berrett-Koehler Publishers, Inc., 2022)
"This complete guide to effective, transformative diversity training provides an answer to the superficial, check-the-box DEI efforts that are undermining the entire field. DEI work is getting a bad reputation. But that's because it's not being done right, say veteran diversity consultants James O. Rodgers and Laura Kangas. Too many organizations are treating diversity training as a quick-hit, low-cost, check-the-box activity. Effective diversity training involves behavioral change based on adult learning theory. It is rigorous, deeply personal, experience based, and, if done well, life changing. Rodgers and Kangas offer a complete guide, from design to implementation to results. They show how to: determine what specific, tangible outcomes an organization wants before it starts; link diversity training to overall organizational strategy; help all participants forge an individual, emotional connection to the training; identify what skills a facilitator needs-the right facilitator makes all the difference; create memorable learning experiences, not simply educational programs. The authors' goal is nothing less than to spark a worldwide revolution of informed practitioners, employees, and business leaders who will demand diversity training be given the same time, resources, and attention as any other critical enterprise initiative. Reading group discussion guide available in book"--